2015
DOI: 10.1515/aot-2015-0036
|View full text |Cite
|
Sign up to set email alerts
|

ITRS lithography roadmap: 2015 challenges

Abstract: In the past few years, novel methods of patterning have made considerable progress. In 2011, extreme ultraviolet (EUV) lithography was the front runner to succeed optical lithography. However, although EUV tools for pilot production capability have been installed, its high volume manufacturing (HVM) readiness continues to be gated by productivity and availability improvements taking longer than expected. In the same time frame, alternative and/or complementary technologies to EUV have made progress. Directed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 2 publications
0
55
0
1
Order By: Relevance
“…Recently, significant improvement in the defect reduction on templates have been reported [40][41][42]. It has been revealed that overall process defectivity has been lessened by two orders of magnitude to 9 defects per cm 2 [43]. Another key issue of NIL that should be realized is nano-defect management (NDM) technology which includes defect inspection of templates and imprinted wafer, the resist material innovation and the defect mitigation.…”
Section: Nanoimprint Lithographymentioning
confidence: 99%
“…Recently, significant improvement in the defect reduction on templates have been reported [40][41][42]. It has been revealed that overall process defectivity has been lessened by two orders of magnitude to 9 defects per cm 2 [43]. Another key issue of NIL that should be realized is nano-defect management (NDM) technology which includes defect inspection of templates and imprinted wafer, the resist material innovation and the defect mitigation.…”
Section: Nanoimprint Lithographymentioning
confidence: 99%
“…[1,2] The extensive and inclusive application of ArF immersion lithography with other resolution enhancement techniques (RETs) make it the most powerful, reliable and economical option from manufacturing perspective. [3] To suppress the impact of reflected light from underneath layers, the reflectivity must be precisely controlled at the interface of the resist and the bottom anti-reflective coating (BARC) layer.…”
Section: Introductionmentioning
confidence: 99%
“…One critical issue in the EUV lithography for high volume manufacturing is development of EUV resists which has the high resolution, high sensitivity and low line-width roughness, and low outgassing, simultaneously [2,3]. Especially, the high sensitivity is strongly required to relax the specification of EUV power and maintain the highlithographic throughput.…”
Section: Introductionmentioning
confidence: 99%